Text and Genre in Reconstruction: Effects of Digitalization on Ideas, Behaviours, Products and Institutions - McCarty, Willard (Open Book Publishers, 2010)
In this broad-reaching, multi-disciplinary collection, leading scholars investigate how the digital medium has altered the way we read and write text. In doing so, it challenges the very notion of scholarship as it has traditionally been imagined. Incorporating scientific, socio-historical, materialist and theoretical approaches, this rich body of work explores topics ranging from how computers have affected our relationship to language, whether the book has become an obsolete object, the nature of online journalism, and the psychology of authorship. The essays offer a significant contribution to the growing debate on how digitization is shaping our collective identity, for better or worse.